Acetylation changes tau interactome to degrade tau in Alzheimer’s disease animal and organoid models - Choi, Heesun (Aging Cell, 2019)
Alzheimer's disease (AD) is an age‐related neurodegenerative disease. The most common pathological hallmarks are amyloid plaques and neurofibrillary tangles in the brain. In the brains of patients with AD, pathological tau is abnormally accumulated causing neuronal loss, synaptic dysfunction, and cognitive decline. We found a histone deacetylase 6 (HDAC6) inhibitor, CKD‐504, changed the tau interactome dramatically to degrade pathological tau not only in AD animal model (ADLP(APT)) brains containing both amyloid plaques and neurofibrillary tangles but also in AD patient‐derived brain organoids. Acetylated tau recruited chaperone proteins such as Hsp40, Hsp70, and Hsp110, and this complex bound to novel tau E3 ligases including UBE2O and RNF14. This complex degraded pathological tau through proteasomal pathway. We also identified the responsible acetylation sites on tau. These dramatic tau‐interactome changes may result in tau degradation, leading to the recovery of synaptic pathology and cognitive decline in the ADLP(APT) mice.